A Call for Onto-Epistemological Diversity in Early Childhood Education and Care: Centering Global South Conceptualizations of Childhood/s. Issue 1 (March 2017) - Pérez, Michelle Salazar; Saavedra, Cinthya M.
In this chapter, we call for onto-epistemological diversity in the field of early childhood education and care (ECEC). Specifically, we discuss the need to center the brilliance of children and communities of color, which we argue, can be facilitated by foregrounding global south perspectives, such as Black and Chicana feminisms. Mainstream perspectives in ECEC, however, have been dominantly constructed from global north perspectives, producing a normalized White, male, middle-class, heterosexual version of childhood, where minoritized children are viewed as deficit. Although there have been important challenges to the discourse of a normalized, deficit child, we argue much of this work has remained grounded in global north positionings, which separate theory from the lived realities of children of color. As such, we introduce Black and Chicana feminisms as global south visions to transform approaches to research and pedagogy in ECEC and, in turn, disrupt inequities.